Use and Overuse of a "Go To" Drug Diane A. Simon. - Simon, Diane A. (Distributed by ERIC Clearinghouse, 2010)
I chose to write my paper on the misuse and misdiagnosis of cognitive pharmaceutical therapies such as Adderall and Ritalin. Though I found several articles, and sources from research relating to the abuse of the drugs, based on the project constraints I was only able to scratch the surface. In addition to peer-reviewed sources, I found several College Universities that have help site for students who have one form of addiction or another, several excerpts were specifically related to Adderall and Ritilan. To this author there was nothing more informative then words directly from an abuser. Therefore, I showcased one particular insert from a college student that was seeking assistant to help her with her addiction. With further research, I was also able to draw on my current position at a family practice taking mental note of patient appointments as well as speak to the physicians that work there. Moreover, an interview was conducted with a psychologist in order to get a specific view of how those sectors of the medical professionals are able to deal with over scripting and abuse. The interview was an insightful look at how difficult it is for him to diagnose, prescribe or determine that these specific drugs are actually being misused. Of further value, is the incorporated statistical chart showing the categories of gender, age and race. The disparity becomes clear between all 3 categories. It was also interesting to see the number of off label uses that Adderall and Ritalin are prescribed for. Increased energy and weight loss are two of the most common usages and unfortunately are the most common abuses. In addition to the above, I also added a section on how to understand the need for these therapies when used responsibly, and a brief overview of what ADHD and ADD are. The paper was written with the intent to bring to light the misuse of pharmaceuticals that were originally created to assist us with cognitive developmental deficiencies. And a further hope that those who in a position to diagnose and treat using these drugs are made aware of the misuse and abuse taking place on college campuses, in the home and on the streets. (Lists 10 resources.)